Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

Write (8a^-3)^2/3 in a simplest form.
a. a^2/4
b. 4a^2
c. 1/4a^2
d. none of these


Sagot :

naǫ
[tex](8a^{-3})^\frac{2}{3}=(8 \cdot \frac{1}{a^3})^\frac{2}{3}=(\frac{8}{a^3})^\frac{2}{3}=\sqrt[3]{(\frac{8}{a^3})^2}=\sqrt[3]{\frac{64}{a^6}}=\frac{\sqrt[3]{64}}{\sqrt[3]{a^6}}=\frac{4}{a^2}[/tex]

It doesn't equal any of the answers A, B, C.
The answer is D.